Epidemiological Characteristics of Infectious Diseases Among Travelers Between China and Foreign Countries Before and During the Early Stage of the COVID-19 Pandemic - Zheng Luo; Wei Wang; Yibo Ding; Jiaxin Xie; Jinhua Lu; Wen Xue; Yichen Chen; Yichen Chen; Ruiping Wang; Xiaopan Li; Xiaopan Li; Lile Wu (Frontiers Media S.A., 2021)
Background: International travel during the Coronavirus disease 2019 (COVID-19) pandemic carries a certain magnitude of infection risk both to travelers and their destination, which may be difficult to assess in the early stage. The characteristics of common infectious diseases of tourists may provide some clues to identify the high-risk travelers and protect susceptible population.Methods: From among 48,444 travelers screened at Shanghai Port, we analyzed 577 travelers with 590 infectious diseases for age, sex, disease type, and World Health Organization (WHO) regions. We used the Joinpoint Regression Program to identify the average percent changes (APC) in the various trends among these individuals.Results: Hepatitis B, syphilis, and HIV were the most common infectious diseases in travelers entering China, and Hepatitis B, pulmonary tuberculosis, and syphilis in Chinese nationals traveling abroad (overall detection rates, 1.43 and 0.74%, respectively; P < 0.05). Africa (2.96%), the Americas (1.68%), and the Western Pacific (1.62%) exhibited the highest detection rates. This trend did not decrease since the COVID-19 pandemic (P > 0.05) and rather showed an upward trend with increasing age [APC 95% CI = 5.46 (3.41,7.56)%, P < 0.05]. However, there were no evident trends in monthly infection rates of travelers exiting and entering China from different WHO regions (all P > 0.05).Conclusion: Travelers always carry a transmission risk of common infectious diseases. It may be reasonable to adjust strategies for airport screening and quarantine according to the age and departure area of travelers to prevent and control new infectious diseases.